An Efficient One-Pot Synthesis of 3,5-Disubstituted 1H-Pyrazoles - Wu, Lei-Lei; Ge, Yi-Cen; He, Ting; Zhang, Lei; Fu, Xing-Li; Fu, Hai-Yan; Chen, Hua; Li, Rui-Xiang (Synthesis, 2012)
An efficient, general, one-pot, three-component procedure for the preparation of 3,5-disubstituted 1H-pyrazoles via condensation of substituted aromatic aldehydes, tosylhydrazine and terminal alkynes in toluene is reported. The reaction tolerates a variety of functional groups and sterically hindered substrates to afford the desired pyrazoles in yields of 67–91%.
Keywords: pyrazoles; heterocycles; condensation; cycloaddition; aldehydes